'A mí, estos pleitos no me interesan': Carlos Saura's Llanto por un bandido and Banditry in the Ominous Decade. Issue 6 (3rd July 2017) - Andrews, Jean
Abstract: This article argues that Carlos Saura's 1964 film biography of the 1830s Andalusian bandit El Tempranillo, Llanto por un bandido, provides an insight into the impact of the War of Independence (1808–1814) and its aftermath on bandits in terms of physical and mental trauma, their involvement in politics and their interaction with civil society. Saura and his co-screenwriter used the French authors Théophile Gautier and Prosper Mérimée in their research on the period, thus incorporating views of Spain emanating from the culture of the Napoleonic aggressor. This, combined with the fact that the incorporation of outlaws into militia resistance was a common feature of the Napoleonic wars, produces a very complex backdrop for the film. If we add to this considerations relevant to censorship of the arts in Spain in the early 1960s, a flawed film which has not been seen as important in Saura's oeuvre becomes a very interesting witness to a century and a half of Spanish history.